2017
DOI: 10.3390/ma10111283
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Fracture Behavior and Failure Mechanism of Additively-Manufactured AISI 4140 Low Alloy Steel by Laser Engineered Net Shaping

Abstract: AISI 4140 powder was directly deposited on AISI 4140 wrought substrate using laser engineered net shaping (LENS) to investigate the compatibility of a LENS-deposited part with the substrate. Tensile testing at room temperature was performed to evaluate the interface bond performance and fracture behavior of the test specimens. All the samples failed within the as-deposited zone, indicating that the interfacial bond is stronger than the interlayer bond inside the deposit. The fracture surfaces were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Stress concentration will distribute around these small QR pixels, i.e. voids, and they can easily lead to the 3D printed component fracture under high static/dynamic loading or fatigue failure due to cyclical stress after long working period [20][21][22]. It is notable that the density requirement of the 3D printed metal component used in the aerospace industry is close to 100%.…”
Section: Reviewermentioning
confidence: 99%
“…Stress concentration will distribute around these small QR pixels, i.e. voids, and they can easily lead to the 3D printed component fracture under high static/dynamic loading or fatigue failure due to cyclical stress after long working period [20][21][22]. It is notable that the density requirement of the 3D printed metal component used in the aerospace industry is close to 100%.…”
Section: Reviewermentioning
confidence: 99%
“…On the one hand, when steel is used for mold and die (especially high carbon steel), it is difficult to deposit many layers on conventional manufacturing substrate without defects, as it is an alloy with high levels of hardness. Simultaneously, the LMD process offers the capability of depositing diverse material, such as interlayer materials [9] and functionally gradient materials [10,11]. This characteristic can be utilized to build dense deposition layers on existing substrate without cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Many test results showed that satisfactory mechanical properties, such as yield strength (YS), ultimate strength (UTS), and hardness can be obtained by laser additive manufacturing for various types of steels [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Many valuable results have been obtained in Cr-Ni-Mo steel via laser additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%